2021
DOI: 10.7554/elife.59775
|View full text |Cite
|
Sign up to set email alerts
|

Cell-density independent increased lymphocyte production and loss rates post-autologous HSCT

Abstract: Lymphocyte numbers need to be quite tightly regulated. It is generally assumed that lymphocyte production and lifespan increase homeostatically when lymphocyte numbers are low, and vice versa return to normal once cell numbers have normalized. This widely-accepted concept is largely based on experiments in mice, but is hardly investigated in vivo in humans. Here we quantified lymphocyte production and loss rates in vivo in patients 0.5-1 year after their autologous hematopoietic stem cell transplantation (auto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…We showed previously that apparent density-dependent effects on naive T cell survival following thymectomy can also be explained by adaptive or selective processes ( den Braber et al, 2012 ; Rane et al, 2018 ). Similarly, in humans, any regulation of a natural set-point appears to be incomplete at best; naive T cell numbers in HIV-infected adults typically do not normalise following antiretroviral therapy ( Hazenberg et al, 2000 ), and recovery from autologous haematopoietic stem cell transplant results in persistent perturbations of T cell dynamics ( Baliu-Piqué et al, 2021 ). Dutilh and de Boer, 2003 showed that explaining the kinetics of decline in TREC frequencies in human naive T cells requires an increase in either cell division or survival with age, as naive T cell numbers decline.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that apparent density-dependent effects on naive T cell survival following thymectomy can also be explained by adaptive or selective processes ( den Braber et al, 2012 ; Rane et al, 2018 ). Similarly, in humans, any regulation of a natural set-point appears to be incomplete at best; naive T cell numbers in HIV-infected adults typically do not normalise following antiretroviral therapy ( Hazenberg et al, 2000 ), and recovery from autologous haematopoietic stem cell transplant results in persistent perturbations of T cell dynamics ( Baliu-Piqué et al, 2021 ). Dutilh and de Boer, 2003 showed that explaining the kinetics of decline in TREC frequencies in human naive T cells requires an increase in either cell division or survival with age, as naive T cell numbers decline.…”
Section: Discussionmentioning
confidence: 99%
“…The memory T-cell pool eventually turns younger due to the presence of a young source. This could present a potential explanation for the observation that reconstituted T-cell pools have higher proliferation rates after autologous stem-cell transplantation ( 11 ) as the highly-divided circulating memory T cells were replaced with lowly-divided memory T cells. Moreover, if the acquisition of different memory T-cell phenotypes were correlated with the division history of a cell ( 73 ), cellular aging would have exciting implications.…”
Section: Discussionmentioning
confidence: 99%
“…Homeostasis need not be perfect, as in both mice and humans, depleted T-cell pools do not always recover to normal levels ( 9 , 10 ). Notably, after autologous stem-cell transplantation, even patients with reconstituted T-cell pools experienced significantly increased T-cell proliferation and loss rates when compared to healthy age-matched controls ( 11 ). These studies highlight our incomplete understanding of the homeostatic process.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless we speculate that the idea of naive T cell homeostasis in the sense of compensatory or quorum sensing behaviour may well be just a theoretical concept in both mice and humans, at least close to healthy conditions. Indeed recently it has been shown that recovery from autologous haematopoietic stem cell transplant results in persistent perturbations of T cell dynamics 39 , arguing against the idea of a naturally regulated set-point. Perhaps a better model is one in which the thymus drives the generation of the bulk of the T cell pool in the early life and thereafter naive T cell repertoires ‘coast’ out into old age in a cell-autonomous manner.…”
Section: Discussionmentioning
confidence: 99%
“…We showed previously that apparent density-dependent effects on naive T cell survival following thymectomy can also be explained by adaptive or selective processes 2,22 . Similarly, in humans, any regulation of a natural set-point appears to be incomplete at best; naive T cell numbers in HIV-infected adults typically do not normalise following antiretroviral therapy 45 , and recovery from autologous haematopoietic stem cell transplant results in persistent perturbations of T cell dynamics 46 . Dutilh et al 47 showed that explaining the kinetics of decline in TREC frequencies in human naive T cells requires an increase in either cell division or survival with age, as naive T cell numbers decline.…”
Section: Discussionmentioning
confidence: 99%